Representative Bureaucracy Among Law Enforcement Agencies: An Analysis of Police Hiring Processes - Milam, Thomas Wesley (My University, 2023)
Public distrust and a reduction in police legitimacy have eroded the public’s perception of police officers, thus creating a sparse applicant pool. Representative bureaucracy theory posits that a public organization should reflect the community the organization serves. Traditionally, the steps a police agency takes to select an applicant for hire can be many, often including difficult obstacles which are used to predict the applicant’s competency and success in law enforcement as a career. These steps test the applicant’s mental and physical ability but can also involve an in-depth investigation into the applicant’s past behaviors and interviews with current police personnel. Each of these steps can vary among police agencies and have various benchmarks and minimum standards that an applicant must achieve before moving on to the next step, which is to ultimately attain employment at the agency. The varied nature of these tests is believed to be rife with subjectivity and highly susceptible to bias. Therefore, an agency may be unfairly eliminating applicants who could perform satisfactorily as an officer (false negative) or could select an applicant who cannot succeed as an officer but only got hired by passing the tests (false positive). This research sought to determine if the steps in a typical hiring process, including written examinations, physical agility examinations, background investigations, and applicant interviews, are contributing to the agency’s hiring of minorities to satisfy the requirements of representative bureaucracy. Through interviewing members of police departments in the southern United States about the hiring process the agency utilizes, these processes were analyzed against standards designed to reduce bias and be effective measures for selecting qualified applicants as police officers.
Keywords: Public administration; Criminology; Dissertations, Academic; Examinations; Employee selection; Police